Marketing Communication Mix on Purchase Decision in Industrial Area: A Study From International Chain Coffee Shop - Filda Rahmiati; Tasya Zahwa Prayoga; Felix Goenadhi; Roszi Naszariah Nasni Naseri (UNIVERSITAS PAKUAN, 2023)
The pandemic has impacted hospitality businesses, including domestic coffee shops, as it is becoming the primary factor in the economic rotation. Starbucks Coffee Indonesia also faces weakened demand from the community to purchase its products. This phenomenon is driven by panic-buying communities who prefer to buy daily necessities. Therefore, this study was conducted to determine the impact of the Marketing Communication Mix aspects, advertising, sales promotion, personal selling, public relations, and direct marketing, as mediated by purchase intention on Starbucks purchase decisions in Cikarang as an Industrial Area. The quantitative method was utilized to gather data using a questionnaire. The questionnaire was distributed online to consumers who purchased Starbucks coffee shop products during the pandemic (n = 188). Structural equation modeling was utilized to determine the proposed research hypothesis. The findings showed that advertising, public relations, and direct marketing positively influence purchase decisions directly and indirectly through Purchase Intention in the industrial region. Sales promotion and personal selling were unimportant in affecting consumer purchase decisions in industrial areas.